Perceived well-being and mental health in haemophilia. Issue 9 (20th October 2020) - Negri, Luca; Buzzi, Andrea; Aru, Anna Brigida; Cannavò, Antonino; Castegnaro, Claudio; Fasulo, Maria Rosaria; Lassandro, Giuseppe; Rocino, Angiola; Santoro, Cristina; Sottilotta, Gianluca; Giordano, Paola; Mazzucconi, Maria Gabriella; et al.
ABSTRACT: The investigation of mental health among persons with haemophilia is mostly focused on negative and disease-related indicators. Literature however shows that psychosocial resources and optimal daily functioning can co-exist with chronic disease. The Dual Continua Model operationalizes positive mental health as 'flourishing', a condition comprising emotional, psychological, and social well-being dimensions. In the present study physical and mental health were comparatively assessed through positive and negative indicators in adults with haemophilia and a control group. Participants included 84 Italian persons with severe haemophilia (Mage = 43.44; SDage = 13.04) and 164 adults without history of chronic illness (Mage = 40.98; SDage = 12.26), who completed the Short Form Health Survey, the Positive and Negative Affect Schedule, and the Mental Health Continuum Short Form. MANOVA and post-hoc t-tests provided evidence of worse general health, lower negative affect and higher psychological well-being among participants with haemophilia compared with the control group. Moreover, the percentage of flourishing individuals was higher among participants with haemophilia. Results support previous evidence suggesting that a chronic disease does not prevent mental well-being attainment. The identification of assets and strengths allowing people with haemophilia to flourish can be fruitfully used to design resource-centered interventions.